Personal Injury Caused by Fires in Residential Buildings in Poland in 2000–2006 - Konciak, Jacek Mikołaj (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The article presents the problem of casualties in fires apartments in Poland in the years 2000–2006. Each year lose their lives in fires about 500 people. Most victims of fires falls on housing, of which 60–70% of these cases the victim is in contact with the fumes and toxic combustion products. The article presents the reasons for such high casualties, and proposes a solution which will significantly contribute to improving the safety of residents.